Caracterização dos blocos cerâmicos estruturais produzidos no Estado do Ceará - Alexandre, Carlos Alberto Bezerra (2017)
Structural masonry as a proposal for a rationalized construction has demonstrated the potential of use in buildings, especially those of low income. The favorable scenario of acceptance of the ceramic block in the national market was established in 2002, due, in particular, to the advent of the Quality Sector Program for the Ceramic Block (PSQ-BC) and the recommendations created by the Caixa Econômica Federal (CEF) for the improvement of habitat quality and productive modernization, being the reference standard for the sector established through NBR 15270 (ABNT, 2005). All this stimulated the growth of the construction system in recent years. Thus, due to the importance of the quality standard of the structural ceramic blocks to be used to compose the structural masonry construction system, in contrast to the lack of studies that reflect in this evaluation, the present work aims to characterize the structural ceramic blocks produced in Ceará, confronting the results with normative standards and found in studies carried out in other Brazilian states, as a way to contribute to the improvement of the production of this type of constructive element in the region. In order to do so, the companies that commercialize this type of constructive component in the state were also listed, as well as samples of both the clay mass and the structural ceramic blocks, for characterization and quality assessment. From the results obtained, it has been verified that the companies produce according to NBR 15270 (ABNT, 2005) for most of the analyzed properties, presenting values of characteristic resistance of the structural ceramic blocks superior to that established by the norm and most of the Brazilian states found in literature. However, regarding the geometric characteristics of the blocks, only two companies met all the normative requirements. In addition, it was concluded that the Statistical Process Control (SPC) proved to be an efficient tool for evaluating the quality of the blocks, since it detected imperceptible failures to the sample analysis.